Minimal important differences for improvement in shoulder condition patient-reported outcomes: a systematic review to inform a BMJ Rapid Recommendation. Issue 2 (20th February 2019) - Hao, Qiukui; Devji, Tahira; Zeraatkar, Dena; Wang, Yuting; Qasim, Anila; Siemieniuk, Reed A C; Vandvik, Per Olav; Lähdeoja, Tuomas; Carrasco-Labra, Alonso; Agoritsas, Thomas; Guyatt, Gordon
Abstract : Objectives: To identify credible anchor-based minimal important differences (MIDs) for patient-reported outcome measures (PROMs) relevant to a BMJ Rapid Recommendations addressing subacromial decompression surgery for shoulder pain. Design: Systematic review. Outcome measures: Estimates of anchor-based MIDs, and their credibility, for PROMs judged by the parallel BMJ Rapid Recommendations panel as important for informing their recommendation (pain, function and health-related quality of life (HRQoL)). Data sources: MEDLINE, EMBASE and PsycINFO up to August 2018. Study selection and review methods: We included original studies of any intervention for shoulder conditions reporting estimates of anchor-based MIDs for relevant PROMs. Two reviewers independently evaluated potentially eligible studies according to predefined selection criteria. Six reviewers, working in pairs, independently extracted data from eligible studies using a predesigned, standardised, pilot-tested extraction form and independently assessed the credibility of included studies using an MID credibility tool. Results: We identified 22 studies involving 5562 patients that reported 74 empirically estimated anchor-based MIDs for 10 candidate instruments to assess shoulder pain, function and HRQoL. We identified MIDs of high credibility for pain and function outcomes and of low credibility for HRQoL. We offered median estimates for the systematic review team who applied these MIDs in Grading of Recommendations Assessment, Development and Evaluation (GRADE) evidence summaries and in their interpretations of results in the linked systematic review addressing the effectiveness of surgery for shoulder pain. Conclusions: Our review provides anchor-based MID estimates, as well as a rating of their credibility, for PROMs for patients with shoulder conditions. The MID estimates inform the interpretation for a linked systematic review and guideline addressing subacromial decompression surgery for shoulder pain, and could also prove useful for authors addressing other interventions for shoulder problems. PROSPERO registration number: CRD42018106531.